Implementasi Kebijakan Alokasi Dana Desa di Desa Pokanbaru Kecamatan Hutabayu Raja Kabupaten Simalungun - Reza Rejeki; Indra Muda; Beby Masitho Batubara (Universitas Medan Area, 2021)
Village Fund Allocation is a fund allocated by the Regency / City Government for the Village sourced from the central and regional financial balance funds received by the Regency / City. Village Fund Management is also not balanced by adequate resources so that the implementation of Human Resources from the apparatus is still not good in terms of skills, expertise and education so that the Village Government Apparatus find it difficult to manage the Village Fund, Low Village Fund Absorption by the Village Government, Village Government Officials who hold concurrent positions in the Village Government bureaucracy. The purpose of this research is to find out the process and factors that hamper the implementation of village fund allocation policies. The implementation of the village fund allocation policy in Pokan Baru Village, Hutabayu Raja District, Simalungun Regency is not good. The quality of human resources from the village head office staff who are still inferior in terms of education and mastering technology is still low so that the implementation of the village fund allocation is not optimal and the human resources of the new pokan village community which is still lacking causes the lack of manpower to carry out the development slow . Disposition of new pokan village head office employees to collaborate is still not good, causing implementation to be slow.